2016
DOI: 10.2106/jbjs.rvw.16.00002
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Total Hip Arthroplasty, Total Knee Arthroplasty, and Unicompartmental Knee Arthroplasty

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(81 citation statements)
references
References 29 publications
1
77
1
2
Order By: Relevance
“…Given the high satisfaction rate and low rate of revision following total joint arthroplasty utilizing contemporary surgical technique and improved biomaterials, protection of the post-operative surgical wound and related complications are of paramount importance. Given the emerging trends of abbreviated inpatient stay following TJA and the increasing percentage of total joint arthroplasty performed in the outpatient setting, the search for reliable chemical anticoagulation agents that reduce VTE events while minimizing post-operative bleeding and wound complications is of great interest [37]. Not all new agents have been able to achieve these objectives consistently; many have been associated with an increased incidence of wound leakage and increased length of stay after total joint replacement [26].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high satisfaction rate and low rate of revision following total joint arthroplasty utilizing contemporary surgical technique and improved biomaterials, protection of the post-operative surgical wound and related complications are of paramount importance. Given the emerging trends of abbreviated inpatient stay following TJA and the increasing percentage of total joint arthroplasty performed in the outpatient setting, the search for reliable chemical anticoagulation agents that reduce VTE events while minimizing post-operative bleeding and wound complications is of great interest [37]. Not all new agents have been able to achieve these objectives consistently; many have been associated with an increased incidence of wound leakage and increased length of stay after total joint replacement [26].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, total hip and total knee arthroplasties (THA and TKA) have transitioned to an outpatient setting, meaning that patients are discharged from hospital on the same day as their procedure. 2 This was initially performed primarily in the US but is now being increasingly performed in Canada and Europe as well. 4…”
Section: Outpatient Arthroplastymentioning
confidence: 99%
“…Success of outpatient THA and TKA has been reported in several studies and is summarized by Pollock et al in a systematic review. 2 All studies discussed in the review were conducted in the US, except for one that investigated outpatient unicompartmental knee arthroplasty in Canada. The authors found the studies reported similar complication rates between outpatient and inpatient groups with significantly lower associated costs for the outpatient group.…”
Section: International Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The use of an arti cial joint is therefore one of the standard surgeries in modern medicine today [1]. Several hundred thousand hip endoprostheses are implanted worldwide every year [2][3][4][5] with sharp increase in demand [5,6].…”
Section: Introductionmentioning
confidence: 99%